A improvisação musical na iniciação coletiva ao violão - Oliveira, Marcelo Mateus de (2012)
The present study sought to examine the role of the collective musical improvisation activity of in the guitar initiation based on the meaning attributed to the by the students for this approach. Seeking to understand the musical learning process emphasizing the educational strategies for teaching. The Knowledge Relationship Theory, Bernard Charlot (2000), and also the Parameters and Principles for Music Education elaborated by Keith Swanwick (1979, 2003) are the theoretical base for our study. During the research we used some categories as activity, sense, call (Charlot, 2000) and composition, assessment, performance and musical discourse (Swanwick, 1979, 2003). The field research was the context of a Guitar Workshop as a university extension course in Music at the federal University of Ceará - Sobral Campus. Methodologically our work uses the action research with its instruments of data collection as questionnaires, interviews and video recording. We concluded analyzing the collected data, that improvisation is important tool for teaching and learning music since the study initiation in the instrument. The possibility of musical background content, engaging in live musical achievements and strengthening the musicianship of the subject are some issues highlighted in our research.